Tool path verification and NC program editing under a multi-window environment - Kim, Chang-Bong; Yang, Min-Yang; Park, Se Hyung (Proceedings of the 1992 Japan - USA Symposium on Flexible Automation Part 1 (of 2), 1992)
NC simulation has been used to replace the test cutting of NC machining. Although it can reduce the NC part programming effort, it still has a problem. If any error is found during the simulation, then the NC code has to be programmed which is time consumming. This paper presents a method for editting the NC code in the verification stage without going back to the part programming stage. A data structure and an algorithm to interactively verify and edit the NC code with the aid of graphics is introduced. The method was implemented as a computer program in a IBM/PC-386 with MS-WINDOW software, and the multi-window function of the MS-WINDOW is used for the simultaneous editing and verification.